Fragility analysis and inelastic seismic performance of steel braced-core-tube frame outrigger tall buildings with passive adaptive negative stiffness damped outrigger. (15th July 2022) - Wang, Meng; Du, Xiu-Li; Sun, Fei-Fei; Nagarajaiah, Satish; Li, Yan-Wen
Abstract: This paper investigated the fragility and inelastic performance of steel braced-core-tube frame outrigger (SBFO) tall buildings with passive adaptive negative stiffness damped outrigger (A-NSDO) systems. The proposed A-NSDO provided passive negative stiffness to achieve substantial damping effect for tall buildings at elastic stage. Once tall buildings was subjected to excessive earthquakes and yielded, the A-NSDO was capable of stiffening the connection between outrigger ends and perimeter columns passively and adaptively to guarantee the integrity of tall buildings. Passive configuration and working mechanism of the A-NSDO were introduced and then its adaptive behavior was validated through experiments. Based on the results of incremental dynamic analysis, fragility analysis of two SBFO structures with different outrigger systems including conventional outrigger, conventional damped outrigger, and A-NSDO, was provided to evaluate structural vulnerability for different limit states like serviceable state, elastic state, plastic state, and collapse state. The inelastic performances SBFO tall buildings with different outrigger systems were discussed in detail, including seismic envelopes, time history results, response spectra, and hysteretic responses of columns, braces, and the A-NSDO. Numerical results validated that the proposed A-NSDO not only took its advantage at elastic states for SBFO tall buildings but was also beneficial during the inelastic states. Highlights: Proposing of A-NSDO with passive adaptive stiffness feature and test validation. IDA and fragility quantification of SBFO tall buildings with A-NSDO. Highlighting the elastic/inelastic responses mitigation of SBFO with A-NSDO. Recognizing the control effect of A-NSDO on inelastic higher modes vibration.